Relações de gênero e sexualidade na educação infantil: interfaces que envolvem as práticas pedagógicas - Oriani, Valéria Pall [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This text is the final version of my Doctoral thesis in Education, developed together with the Graduate Program of the Faculty of Philosophy and Sciences - Universidade Estadual Paulista Julio de Mesquita Filho campus of Marilia (SP), Brazil. My main goals were to raise the perceptions of the teacher on gender relations and sexuality in pedagogical practices in childhood education; to understand the manifestations of sexuality in children at this level of schooling, as well as the actions of the professionals in face of these events; to problematize gender relations within childhood education considering the discussions around caring and educating. To achieve the proposed goals I resorted of interviews with educators that work inside two educational institutions selected as research site, and also with professionals linked to the Municipal Education Network of the city of Marilia (SP). Moreover, I counted on interviews with two students of the University who work directly with the issue and have a concern for the continued formation of teachers. Guided by the analysis of the speeches from my interviewees and by theoretical support that encompasses benchmark scholars on the proposed research subject, I was able to ascertain that the pedagogical practices developed at school can reinforce stereotypes historically constructed in social relationships. The school reproduces sexist practices found in society in general and may work in favor of the permanence of discrimination and prejudices related to gender identity. However, I support the idea that it is possible to educate for transformation, if there is a change in mentality that is beyond the reformulation of curricula in teacher formation courses. Among the contributions that this work can bring to the scientific community are the following: to highlight a yet explored object in the academic environment; to bring elements for reflection that may guide the reformulation of curricula in...

Este texto é a versão final de tese de Doutorado em Educação, desenvolvida junto ao Programa de Pós Graduação da Faculdade de Filosofia e Ciências - Universidade Estadual Paulista Júlio de Mesquita Filho, campus de Marília (SP), Brasil. Tive como principais objetivos: levantar quais são as percepções de educadores sobre relações de gênero e sexualidade nas práticas pedagógicas na educação infantil; compreender as manifestações da sexualidade das crianças neste nível de escolarização, bem como a atuação dos/das profissionais diante dessas manifestações; problematizar as relações de gênero no espaço da educação infantil, considerando as discussões em torno do cuidar e do educar. Para atingir os objetivos propostos fiz uso de entrevistas com educadores que trabalham tanto no interior de duas instituições escolares selecionadas como universo de pesquisa, quanto de profissionais vinculados à Rede Municipal de Ensino da cidade de Marília (SP). Contei, ainda, com entrevistas feitas com dois estudiosos da Universidade que trabalham diretamente com a temática e possuem uma preocupação com a formação continuada de professores. Pautada na análise das falas de meus entrevistados e em suporte teórico que engloba estudiosos de referência sobre o objeto de pesquisa proposto, pude verificar que as práticas pedagógicas desenvolvidas no espaço escolar podem reforçar estereótipos construídos historicamente nas relações sociais. A escola reproduz práticas sexistas presentes na sociedade em geral e pode trabalhar a favor da permanência de discriminações e preconceitos referentes à identidade de gênero. Contudo, defendo a ideia de que é possível educar para a transformação, se houver uma mudança de mentalidade que está além da reformulação de currículos em cursos de formação de professores. Entre as contribuições que este trabalho pode trazer para a comunidade científica estão:...
Keywords: Educação de crianças; Relações de gênero; Sexo; Pratica de ensino; Education